Stability and Hopf Bifurcation of Delayed Variable Frequency Water-Supply System - DING Yu-ting; JIANG Li; SU Lin-lin (Journal of Harbin University of Science and Technology)
This paper considers the mathematical model of variable frequency water supply system in the process of applying glue to artificial board. On the basis of the original linear model，the effects of time delay and the nonlinear factors are considered. Then we get the delayed nonlinear differential equation of variable frequency water-supply system. Further，we consider the existence and stability of the equilibrium and the Hopf bifurcation in this equation，and derive the normal form of the Hopf bifurcation by using the multiple time scales method. Finally， by using Matlab software，we obtain numerical simulations under actual parameters，and we show the existence of stable equilibrium and stable periodic solutions of the system to verify the correctness of the theoretical analysis.